2009
DOI: 10.1590/s0006-87052009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia de herbicidas em diferentes quantidades de palha de cana-de-açúcar no controle de Ipomoea grandifolia

Abstract: ) aplicados em pré-emergência de I. grandifolia e de cinco quantidades de palha de cana-de-açúcar (0, 5, 10, 15 e 20 t ha -1 ). A eficácia de controle das plantas daninhas foi avaliada aos 7, 14, 21 e 28 dias após a aplicação dos tratamentos (DAT). Com a adição de palha (15 e 20 t ha -1 ) ao solo foi reduzida a população de I. grandifolia. À medida que a quantidade de palha foi aumentada, reduziu-se a eficácia dos herbicidas; com 15 t ha -1 de palha, o controle foi considerado insatisfatório para todos os trat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
3
0
9
Order By: Relevance
“…Martins et al (1999) have found that non even 15 t ha -1 of sugarcane straw are sufficient to inhibit the germination and emergence of E. heterophylla. For I. triloba, Monquero et al (2009) ) reduce the infestation of this species.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Martins et al (1999) have found that non even 15 t ha -1 of sugarcane straw are sufficient to inhibit the germination and emergence of E. heterophylla. For I. triloba, Monquero et al (2009) ) reduce the infestation of this species.…”
Section: Resultsmentioning
confidence: 95%
“…This vegetable waste deposited on the soil changes in a way its microclimate, changing the brightness, temperature and humidity, key elements in the control of dormancy and germination of weed seeds (Correia & Rezende, 2002;Christofoletti et al, 2009). Among the species that tend to remain as weeds in the raw sugarcane system are Ipomoea triloba (known by several common names, including littlebell and Aiea morning glory) and Euphorbia heterophylla (known under the common names of (Mexican) Fireplant, Painted Euphorbia, Japanese Poinsettia, Desert Poinsettia, Wild Poinsettia, Fire on the Mountain, Paintedleaf, Painted Spurge, Milkweed, and Kaliko Plant) (Martins et al, 1999;Monquero et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A eficácia dos demais herbicidas não foi afetada pela ausência ou presença de palha nas quantidades estudas (Tabela 2). Monquero et al (2009c) com a mesma planta daninha, os pesquisadores observaram que quantidades crescentes de palha reduziram o controle de I. triloba por essa mistura, fato esse explicado pela baixa precipitação no ensaio após a aplicação dos herbicidas (9 mm), mostrando a importância da precipitação para lavar o produto da palha e levá-lo até o solo. Em outro estudo de eficácia de herbicidas aplicados em pré-emergência sobre a palha de cana-de-açúcar, Monquero et al (2009b) relataram que o herbicida mesotrione teve a eficácia alterada pela presença de palha, sendo positiva no controle de Bidens pilosa e negativa no controle de I. quamoclit.…”
Section: Resultsunclassified
“…Essa palhada afeta drasticamente e de diferentes maneiras o estabelecimento de plantas daninhas em áreas cultivadas. Dentre elas, citam-se a limitação de variação da temperatura na superfície do solo; a formação de uma barreira física a ser transposta pela planta em crescimento; o aumento da quantidade de microrganismos que podem decompor as sementes dessas plantas; e os possíveis efeitos alelopáticos que inibem a germinação (Negrisoli et al, 2007a).…”
Section: Introductionunclassified
“…Increased infestation of these weeds in areas of mechanically harvested sugarcane crops can be explained by some aspects of the biology of these plants, such as their large seed-reserve structures, capable of growing through a layer of straw on the soil, in addition to their negative photoblastic behavior (Monquero et al, 2009). Weed control using chemical methods is increasingly significant in sugar cane crop.…”
Section: Introductionmentioning
confidence: 99%